Complexity in decision making: Determining university library opening hours. (June 2019) - Ravenwood, Clare; Walton, Graham; Stephens, Derek
Making decisions on academic library opening hours is complex with many pressures on managers. This research surveys senior academic library managers from the UK, using a questionnaire to reveal views on library opening hours, the decision-making process, and the pressures which influenced their decisions. A variety of factors were found, in particular satisfying undergraduate demands. The research also revealed the sources of information important in making decisions on opening hours and the influence of 'political' issues in the decision-making process. Some institutions remove complexity by utilising 24/7 opening, though this is not an option for many.